2021
DOI: 10.3389/fcvm.2021.713341
|View full text |Cite
|
Sign up to set email alerts
|

5 Year Outcomes of Patients With Aortic Structural Valve Deterioration Treated With Transcatheter Valve in Valve – A Single Center Prospective Registry

Abstract: The Valve-in-Valve (ViV) technique is an established alternative for the treatment of structural bioprosthetic valve deterioration (SVD). Data describing the intermediate term follow up of patients treated with this approach is scarce. We report on our intermediate-term outcomes of patients with SVD in the Aortic position treated with ViV. Included were patients with symptomatic SVD in the aortic position valve who were treated by Valve in valve transcatheter aortic valve implantation (ViV-TAVI) during the yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In the Global Valve-in-Valve Registry, 5% of patients had ≥+2 degree of AR after the procedure [21]. Similarly, in a recent study 3.7% of patients treated with the same intervention reported moderate AR at one-year [22]. Finally, a study from Cleveland showed the presence of moderate-severe aortic regurgitation in 30.4% of patients undergoing ViV-TAVI [23].…”
Section: Discussionmentioning
confidence: 89%
“…In the Global Valve-in-Valve Registry, 5% of patients had ≥+2 degree of AR after the procedure [21]. Similarly, in a recent study 3.7% of patients treated with the same intervention reported moderate AR at one-year [22]. Finally, a study from Cleveland showed the presence of moderate-severe aortic regurgitation in 30.4% of patients undergoing ViV-TAVI [23].…”
Section: Discussionmentioning
confidence: 89%
“…Despite the risk of valve-invalve TAVI-associated coronary occlusion, attributed to previous degenerated prosthetic valve leaflets obstructing the left ostia, literature is demonstrating TAVI-in-TAVI to be technically feasible with comprehensive preoperative assessment and developing TAVI valves. 36,37 Although evidence has demonstrated that aortic valve intervention of dialysis-dependent patients with aortic stenosis leads to increased survival, the postoperative prognosis remains unfortunate in this subset of patients. 38 A study published in 2022 retrospectively analysed the 3year survival of dialysis-dependent patients who received either AVR or TAVI (1020, 1280, respectively) with a median age of 79.47 and 75.45, respectively.…”
Section: Discussionmentioning
confidence: 99%